Hubungan Sosial di Era Teknologi: Ketika Koneksi Tidak Menjamin Interaksi yang Dekat - Linda Herawati, Ni Made Linda; Sujana, I Putu Windu Mertha; Yudana, I Made (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2026)
Interaction is how people socialize to build relationships. Digitalization has made interaction limitless, but there's a social relationship paradox in the tech era, where even though digital connectivity is growing, the depth of interaction and emotional closeness often fade. This highlights a fundamental shift in how people build and maintain interpersonal relationships amid the dominance of social media and digital devices. This research argues that the ease of access and frequency of online interactions do not always correlate with the quality of substantial relationships. Instead, reduced digital interactions often overlook the nuances of non-verbal communication and physical presence that are crucial for empathy and emotional closeness. The article also highlights how social media algorithms, the pressure for online validation, and phenomena like FOMO (Fear of Missing Out) can contribute to social isolation and anxiety, even though individuals appear to be “connected” to thousands of people. Using a qualitative and descriptive approach, along with conceptual studies and analysis, this article aims to describe the challenges of achieving authentic closeness amid the chaos of digital connectivity, and to explore solutions on how technology can be leveraged to strengthen, rather than weaken, meaningful social bonds.